SOCIOLINGUISTIC STUDY OF MONGONDOW LANGUAGE VARIATIONS IN THE YOUNGER GENERATION IN PANGIAN - Joshua KA Loho; Santje Iroth; Donal M. Ratu (Journal of Higher Education and Academic Advancement, 2024)
This research aims to describe variations of the Mongondow language among the younger generation in Pangian using sociolinguistic studies. This research uses the listening and professional method to examine language variations by listening to spoken symbols in the language and understanding the meaning of the communication that has been conveyed. The source of data obtained is primary data collected through direct observation. The data collection techniques used in the listening method are observation, recording and note-taking, then in the professional method using fishing techniques and face-to-face techniques. The data analysis used is a matching technique to analyze language by using language as a reference. Then, from the data that has been found, data classification and data presentation will be carried out informally. This research was carried out from April to May 2023 in Pangian Bersatu village. The results of this research show that the use of the Mongondow language among the younger generation in Pangian Bersatu village is still inherent. This is based on variations in ideolect, dialect, chronolect and sociolect used by the younger generation in Pangian Bersatu village in daily conversation with language styles that vary according to the speech acts used in each area in Pangian Bersatu village. These findings provide an overview of how the Mongondow language varies and provides benefits for educational institutions as a reference for research on language variations as well as sociolinguistic studies as the science of studying language and the social interactions of its people.